2001
DOI: 10.1021/ja004138t
|View full text |Cite
|
Sign up to set email alerts
|

Mesoporous Aluminosilicates with Ordered Hexagonal Structure, Strong Acidity, and Extraordinary Hydrothermal Stability at High Temperatures

Abstract: Highly ordered hexagonal mesoporous aluminosilicates (MAS-5) with uniform pore sizes have been successfully synthesized from assembly of preformed aluminosilcate precursors with cetyltrimethylammonium bromide (CTAB) surfactant. The aluminosilicate precursors were obtained by heating, at 100--140 degrees C for 2--10 h, aluminasilica gels at the Al(2)O(3)/SiO(2)/TEAOH/H(2)O molar ratios of 1.0/7.0--350/10.0--33.0/500--2000. Mesoporous MAS-5 shows extraordinary stability both in boiling water (over 300 h) and in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
203
0
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 350 publications
(209 citation statements)
references
References 33 publications
5
203
0
1
Order By: Relevance
“…4). We also found that this band for Ti-MCM-41 and Ti-SBA is between 1100 and 1110 cm -1 [50][51][52], always lower than 1125 cm -1 . This difference in frequency essentially reflects the different coordination of titanium ions.…”
Section: Titanium Species On Siosupporting
confidence: 54%
“…4). We also found that this band for Ti-MCM-41 and Ti-SBA is between 1100 and 1110 cm -1 [50][51][52], always lower than 1125 cm -1 . This difference in frequency essentially reflects the different coordination of titanium ions.…”
Section: Titanium Species On Siosupporting
confidence: 54%
“…After then, multi-step synthesis strategies for assembling preformed zeolite seeds into a mesoporous structure were proposed in order to prevent the separate formation of zeolite and mesoporous silica [61][62][63][64]. In a modified method, Naik et al performed steam-assisted crystallization (i.e., dry-gel synthesis) of zeolite seeds that were preassembled by surfactants [65].…”
Section: Soft-templating Routementioning
confidence: 99%
“…Mesoporous materials have good surface area, high thermal stability, good acid sites and uniform pore size 6 . Aluminium incorporated mesoporous materials were initially reported by Corma et al 3 .…”
Section: -5mentioning
confidence: 99%